Empowerment of Joint Business Groups (KUBE) of the Dalang Collection Waste Bank Based on Digital Affiliate Marketing: Pemberdayaan Kelompok Usaha Bersama (KUBE) Bank Sampah Dalang Collectiong Berbasis Digital Affiliate Marketing - Saputra, Candra; Suryani, Suryani; Bayu Azhar; Lisda Lestari; Zahara Clamiza (Universitas Lancang Kuning, 2024)
The problem with KUBE Dalang Collection's partners is that waste management in Pekanbaru City has not been implemented optimally, where 20% of people are smart about utilizing waste banks in Pekanbaru City. Besides that, the partners also experience the low ability of the existing KUBE groups to carry out the waste bank creative production process, Not yet maximized the craft production process for all KUBE groups under the guidance of Dalang Collection, Insufficient number of KUBE groups carrying out the waste bank creative product production process and 4 .There is still no platform used in order to increase sales and marketing of products produced in the KUBE group. The purpose of the activities carried out is to increase the production and marketing capabilities of the Joint Business Group (KUBE) Dalang Collection Garbage Bank with an approach based on Digital Affiliate Marketing. The Program Activities carried out include: 1). Bridging Program, Mapping the Supply of Waste Raw Materials and Waste Bank Production Training, 2). Community Empowerment-Based New KUBE Group Decentralization Program and 3). Marketing Improvement Program through the Development of the “BASADA” Digital Affiliate Marketing Platform. Outcomes achieved from the activities carried out include: 1). There has been an increase in the ability of the KUBE Dalang Collection community in the field of production and marketing where there are 10 KUBE products, 2). There are 5 KUBE groups that are members of affiliate marketing, and 3) There is a Web-based BASADA application product used by partners in marketing KUBE products